2012
DOI: 10.1590/s0100-204x2012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Densidade de plantas em híbridos de milho semeados no final do inverno em ambientes irrigados e de sequeiro

Abstract: Plant density of maize hybrids sowed during late winter in irrigated and rainfed environmentsAbstract -The objective of this work was to determine plant density of maize hybrids sowed early (August and and was obtained with densities higher than nine plants per square meter, regardless of water availability and hybrid. The use of high densities is an efficient strategy to optimize maize grain yield sowed during late winter in the warmer regions of the South of Brazil, as long as there is no water deficit betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
3
15
0
6
Order By: Relevance
“…This value was 15% higher compared with irrigation only during critical periods of the culture, which produced an average of 406 grains per ear. Serpa et al (2012) also found that the NGE decreased linearly with an increase in the density of plants, for two of the four hybrids tested, partially corroborating the results observed in our study.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This value was 15% higher compared with irrigation only during critical periods of the culture, which produced an average of 406 grains per ear. Serpa et al (2012) also found that the NGE decreased linearly with an increase in the density of plants, for two of the four hybrids tested, partially corroborating the results observed in our study.…”
Section: Resultssupporting
confidence: 91%
“…At a density of four plants per m -2 (D1), the highest NGE was observed at an irrigation level of 75% of Et c . Serpa et al (2012) compared the density of hybrid plants, with full irrigation during critical periods of culture, and observed that the NGE was positively affected by irrigation in the first year of the study. They also observed an average of 469 grains per ear for the fully irrigated treatment over the two years of the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations